Modern Banking and OTC Derivatives Markets : The Transformation of Global Finance and its Implications for Systemic Risk - Drees, Burkhard (Occasional Papers; Occasional Paper, 2001)
This chapter provides an overview of market practices, market structure, and official supervision and regulation in financial markets. This paper also highlights the key features of modern banking and over the counter (OTC) derivatives markets that seem to be relevant for assessing their functioning, their implications for systemic financial risks in the international financial system, and areas where improvements in ensuring financial stability can be obtained. The paper also describes how OTC derivatives activities have transformed modern financial intermediation and discusses how internationally active financial institutions have become exposed to additional sources of instability because of their large and dynamic exposures to the counterparty (credit) risks embodied in their OTC derivatives activities. In order to rebalance private and official roles, it is essential first to clarify the limits to market discipline in OTC derivatives markets, before leaning more heavily on aspects of market discipline that seem to work well in these markets.